Endoscopy-assisted removal of periorbital inclusion cysts in children (2011)
Surgical treatment for periorbital inclusion cysts typically involves a brow, pterional, or partial bicoronal scalp incision for sufficient exposure. The authors have recently employed an endoscopy-assisted technique as an alternative approach intended to minimize the length of the skin incision and avoid scarring in the brow. Children having typical clinical findings of a dermoid cyst located on the hairless forehead were selected to undergo endoscopy-assisted cyst removal. For suspected intradiploic lesions, MR imaging was used to assess osseous involvement. After induction of general anesthesia, a 1–2-cm curvilinear incision was made posterior to the hairline. A 30°-angled endoscope (4 mm) was then used for dissection in the subgaleal compartment. Subgaleal dissection was followed by a circumferential periosteal incision in which the authors used an angled needle-tip unipolar cautery. For lesions within the diploe, a high-speed air drill was used to expose the lesion. Complete removal was accomplished with curettage of either the skull or dural surface. Eight patients (5–33 months of age) underwent outpatient endoscopic resection. Seven cysts were extracranial, and 1 cyst extended through the inner table. In all patients complete excision of the cyst was achieved. There was negligible blood loss, no dural violation, and no postoperative infection. There have been no recurrences at a mean follow-up of 15 months. Endoscopy-assisted resection of inclusion cysts of the scalp and calvaria is a safe and effective surgical approach. The technique results in negligible incisions with less apparent scarring compared with previously described incisions. This limited-access technique does not appear to be associated with a higher incidence of cyst recurrence.